The dependence of the amino acid backbone conformation on the translated synonymous codon is not statistically significant - Javier González-Delgado; Pablo Mier; Pau Bernadó; Pierre Neuvial; Juan Cortés (Proceedings of the National Academy of Sciences, 2025)
The correlation between synonymous codon usage and secondary structure in translated proteins has been widely demonstrated. This usage plays a capital role in tuning translational rates and protein folding kinetics, indirectly influencing multiple biological processes. A recent report [A. A. Rosenberg, A. Marx, A. M. Bronstein, Nat. Commun. 13 , 2815 (2022).] suggests that the translated synonymous codon influences the ( ϕ , ψ ) dihedral angles within secondary structure elements. If true, this conclusion would have strong consequences in several scientific fields, including structural biology and protein design, where results would depend on DNA sequence rather than protein sequence. Here, we show that the original statistical methodology used in the referred study was formally incorrect. Furthermore, when using a correct approach, we demonstrate that the influence of the codon on the distribution of the dihedral angles is not statistically significant for any type of secondary structure.